Cover. Issue 1 (23rd January 2020) - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al.
Abstract : The cover image is based on the Original Article Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1 by Mao Lin et al., https://doi.org/10.1002/mgg3.1023 .